Analysis of morphological errors in university research papers by female students of the Arabic language education department at Al-Raya University - Amelia, Fitri; Bakhiet, Bakri Muhammad; Chamidah, Dewi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study investigates morphological errors in academic writings by students in the Arabic Language Teaching Department at Al-Raya University. Despite the university’s strong commitment to promoting Arabic proficiency and providing an Arabic-speaking environment, students still make significant morphological errors in their research papers. These errors, especially in the use of correct word forms, significantly impact the clarity and accuracy of their work. The research identifies and classifies common morphological mistakes such as incorrect derivations, verb usage, and the application of prefixes and suffixes. Such errors can change the meaning of words, leading to incorrect interpretations of academic content. For instance, using the word